Investigation of groundwater table under rock slope by using electrical resistivity imaging at Sri Jaya, Pahang, Malaysia - Haryati, Awang; A F, Salmanfarsi; M S I, Zaini; M A F, Mohamad Yazid; Mohd Idris, Ali (IOP Science, 2021)
Over the years, rock slope will undergo the natural phenomenon of weathering, leading to the weakening of strength and physical properties of the slope material. In Malaysia, one of the causes of the weathering of rock is due to the presence of water, which can form groundwater table in the subsurface of rock slopes. The weathering of rock material in slopes can have significant effect on the stability. In Sri Jaya, Pahang, a large body of rock is exposed in cut slope, where different weathering grade was observed on the surface. The study aims to investigate the groundwater table under the rock slope surface and determine the extent of weathering of the rock slope. For that purpose, the electrical resistivity imaging (ERI)was chosen as a geophysical method to map the subsurface condition of the slope. Resistivity values from the survey were interpreted based on established work that correlates weathering condition of rock material with resistivity value. Different zones of weathering grade and groundwater were determined based from the profile.